6-[F18]Fluoro-L-DOPA and Cerebral Blood Flow in Unilaterally MPTP-Treated Monkeys. (1993) - Doudet, Doris J.; Wyatt, Richard Jed; Cannon-Spoor, Eleanor; Suddath, Richard; McLellan, Catherine A.; Cohen, Robert M.
Abstract : Intravenous administration of O 15 -labeled water and 6-[ F 18 ] -L-fluorodopa were used to assess abnormal striatal activity in monkeys after long-term recovery of unilateral lesions of the dopaminergic nigro-striatal system induced by the neurotoxin MPTP. PET data were examined in relation to behavioral and biological parameters. Cerebral blood flow and 6-[ F 18 ] -L-DOPA uptake were found to be significantly reduced in the lesioned striatum, compared to the unaffected side and to normal controls. There was no correlation between cerebral blood flow and any of the behavioral parameters. The uptake rate constant of F 18 -DOPA from blood to striatum and the ratios of striatum to occipital areas were highly correlated to the concentrations of homovanillic acid in the cerebrospinal fluid of the same animals but not to the rotational behavior. This MPTP-inducedmodei of striatal dopamine deficiency in primates presents similarities with idiopathic Parkinson's disease and may be used to evaluate the effects of dopaminergic lesions and transplants on brain function.